If f ( x ) = ( x + 2 ) x − 2 , then what is the value of f ′ ( 1 1 ) ?
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
f(x)= (x+2)*(x-2)^.5 --------eq. 1
Let (x-2)^.5=y That makes x-2=y^2 which makes x+2=y^2+4
Taking the derivative of this relation between gives us dx=2y*dy Hence, dy/dx= 1/2y
The derivative of y is 0.5/(x-2)^.5
Substituting y in equation 1 gives you f(x)= (y*(y^2+4) = y^3+4y
Now finding the derivative of f(x) gives us f'(x) =(3y^2 + 4) (dy/dx) Substituting x back gives f'(x)=(3(x-2)+4) (1/(2(x-2)^.5)) Putting x=11 we get 31/6
how ? x+2=y^2+4
What?
Y'(x) = f(x).g '(x) + f '(x).g(x)
(x-2).1/2(x-2)^-1/2 .1 + 1.(x-2)^1/2
Y '(11) = 9/2 (11-2)^1/2 + 9^1/2 = 9+ 18/6 = 27/6
my calculations are wrong ?
If y = uv then apply UV rule --> u * dv/dx + v * du/dx
Problem Loading...
Note Loading...
Set Loading...
F ( x ) = ( x + 2 ) ∗ x − 2 F ( x ) = ( x + 2 ) ∗ ( x − 2 ) 2 1 N o w w e t a k e t h e d e r i v a t i v e f ( x ) = ( x + 2 ) a n d g ( x ) = ( x − 2 ) 2 1 F ′ ( x ) = f ′ ( x ) ∗ g ( x ) + f ( x ) ∗ g ′ ( x ) F ′ ( x ) = 1 ∗ ( x − 2 ) 2 1 + ( x + 2 ) ∗ ( 2 1 ( x − 2 ) − 2 1 ) ∗ 1 F ′ ( x ) = x − 2 + 2 x − 2 x + 2 N o w w e s u b s t i t i t e F ′ ( 1 1 ) = 1 1 − 2 + 2 1 1 − 2 1 1 + 2 F ′ ( 1 1 ) = 9 + 2 9 1 3 F ′ ( 1 1 ) = 3 + 6 1 3 F ′ ( 1 1 ) = 6 1 8 + 1 3 F ′ ( 1 1 ) = 6 3 6